Kejadian Diare pada Balita dan Faktor Risikonya - Oktavianisya, Nelyta; Yasin, Zakiyah; Aliftitah, Sugesti (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2023)
Diarrhea is a health problem that often occurs in society, diarrhea is still a major cause of morbidity and mortality in toddlers in various countries, especially in developing countries. The aim of this study was to analyze the factors that cause diarrhea in toddlers. This research is an analytical research with a case control approach. The population of this study was mothers who had toddlers aged 1-5 years who suffered from diarrhea in area of Puskesmas Ganding, Sumenep. The case group was the group of mothers who had children aged 1-5 years who suffered from diarrhea (83 people) and the control group was the group of mothers who had children aged 1-5 years who did not suffer from diarrhea (83 people). The sampling technique is simple random sampling and the data collecting technique used was questionnaire. Data analysis was univariable, bivariable (chi-square) and multivariable analysis with logistic regression test. The results showed that the variables that influence the incidence of diarrhea were water sources p-value 0.007, type of fecal disposal p-value 0.043, waste water disposal p-value 0.020, floor type p-value 0.029, exclusive breastfeeding p-value 0.004 and hand washing behavior p-value 0.019. The results of the multivariate analysis of exclusive breastfeeding had the highest risk of diarrhea (OR=2.86). Exclusive breastfeeding is the most dominant factor influencing the incidence of diarrhea. Exclusive breastfeeding is a protective factor for diarrhea in toddlers, so exclusive breastfeeding reduces or prevents diarrhea in toddlers. Abstrak Diare menjadi masalah kesehatan yang sering terjadi pada masyarakat, diare masih merupakan penyebab utama kesakitan dan kematian pada balita di berbagai negara salah satunya di negara berkembang. Tujuan penelitian ini adalah menganalisis factor penyebab diare pada balita. Penelitian ini merupakan penelitian analitik dengan pendekatan case control. Populasi penelitian adalah seluruh ibu yang mempunyai balita berusia 1-5 tahun yang menderita penyakit Diare di Wilayah Kerja Puskesmas Ganding Kabupaten Sumenep. Kelompok kasus adalah kelompok ibu yang mempunyai balita berusia 1-5 tahun yang menderita penyakit Diare (83 orang) dan kelompok control adalah kelompok ibu yang mempunyai balita berusia 1-5 tahun yang tidak menderita penyakit Diare (83 orang). Teknik pengambilan sampel adalah simple random sampling dan teknik pengumpulan menggunakan kuesioner. Analisis data yaitu univariabel, bivariabel (chi-square) dan analisis multivariable dengan uji regresi logistik.Hasil penelitian didapatkan variabel yang berpengaruh terhadap kejadian diare adalah Sumber Air p-value 0,007, jenis pembuangan tinja p-value 0,043, pembuangan air limbah p-value 0,020, jenis lantai p-value 0,029, pemberian ASI Eksklusif 0,004 dan perilaku mencuci tangan p-value 0,019. Hasil analisis multivariate pemberian ASI Eklusif memiliki besar risiko paling tinggi terhadap kejadian diare (OR=2,86). Pemberian ASI Eklusif merupakan faktor yang paling dominan berpengaruh terhadap kejadian diare. Pemberian ASI Eksklusif merupakan factor protektif untuk kejadian diare pada bayi, sehingga pemberian ASI Eksklusif menurunkan atau mencegah terjadinya diare pada bayi.